The effect of guided inquiry learning model on students' mathematical critical thinking abilities - Ervina Farahnaz Simatupang; Nurhanurawati; Agung Putra Wijaya (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
Mathematics is an abstract discipline that requires higher-order thinking skills, particularly mathematical critical thinking, to be meaningfully understood. However, students' mathematical critical thinking skills in Indonesia remain relatively low. This study aimed to examine the effect of the Guided Inquiry learning model on students' mathematical critical thinking skills. The population of this study consisted of all eighth-grade students at a junior high school in Lampung Province, totaling 192 students distributed across six classes (VIII-A to VIII-F). The sample was selected using a cluster random sampling technique, resulting in 25 students from class VIII-D as the experimental group and 27 students from class VIII-B as the control group. This study employed a pretest–posttest control group design. Quantitative data were collected through essay-type pretests and posttests. Based on the results of the hypothesis testing using the Mann–Whitney U test at a significance level of α = 0.05, the median N-gain of students' mathematical critical thinking skills in the Guided Inquiry group was higher than that of students who experienced conventional learning. These findings indicate that the application of the Guided Inquiry learning model has a positive effect on improving students' mathematical critical thinking skills.